The effects of phonological similarity on the semantic categorisation of pictorial and lexical stimuli: evidence from continuous behavioural measures. Issue 2 (17th February 2016) - Barca, Laura; Benedetti, Filippo; Pezzulo, Giovanni
ABSTRACT: Behavioural and neuroimaging studies provide evidence of automatic activation of phonology (e.g., covert speech) during the recognition of lexical stimuli. Implicit processing of phonological information was investigated in a kinematic study of semantic categorisation of pictures (session A) or words (session B). Participants clicked one of two items (target and distractor) based on their semantic congruency (artefact or natural) with a cued-word. Phonological similarity between cued-word and distractor was varied. The presence of the phonological distractor produced trajectories with greater curvature towards the competing semantic category than did the presence of a distractor not phonologically related. This suggests that the semantic categorisation of pictorial and lexical stimuli is influenced by the automatic activation of phonological information. Trajectories' curvature reveals competition between partially activated phonological and semantic representations suggesting that phonological codes involved in linguistic processing influence the dynamic competition underlying the semantic categorisation of lexical and pictorial.